Equity, envy and efficiency under asymmetric information - Geoffroy de Clippel (Brown University, Department of Economics, 2004)
The set of fair (i.e. envy free and efficient) allocation rules may be empty in wellbehaved pure exchange economies if the agents are asymmetrically informed at the time of contracting. In addition, there may exist efficient allocation rules such that every agent envies another.
Keywords: 330; Asymmetrische Information; Tauschwirtschaft; Gerechtigkeit; Allokationseffizienz